The Process of Learning English in Ngargogondo Borobudur as Desa Bahasa - , ZULVIDA NURAENI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper aims to explain the programs and the learning process in Desa Bahasa Ngargogondo, including the methods of learning that they use, and also the purpose of learning methods. The methods of collecting data are direct observation, interview, and library research. Direct observation was conducted for three months to get a valid information for the programs and the learning process in Desa Bahasa Ngargogondo. Then, interview was conducted with the founder and staff of Desa Bahasa Ngargogondo to get the data and get more information about Desa Bahasa. The last is library research about book of learning